Social Acceptability of Management Actions for Addressing Different Conflict Scenarios Between Humans and Wildlife in Patagonia - Zorondo-Rodriguez, F (Routledge, 2020)
Conflicts between humans and wildlife could generate problems for biodiversity, and conflict management is important for avoiding biodiversity loss. Social acceptability of management actions for mitigating these conflicts can influence the success of wild carnivore management. Our study was carried out in southern Chile where we evaluated levels of social acceptability and consensus (using PCI2) for frightening, relocating, and lethal control in different scenarios for conflicts with pumas and foxes (native species), and feral dogs. Frightening or relocating wild carnivores were more socially acceptable than to not carry out any actions. In comparison to non-ranchers, ranchers were more likely to accept lethal control for feral dogs. Finally, ranchers were more accepting of lethal control for feral dogs rather than lethal control for native carnivores. We found that social group (ranchers or non-ranchers), type of encounter scenario, and carnivore type influenced the social acceptability of different management actions. © 2019, © 2019 Taylor & Francis Group, LLC.